Evaluation of the use of the essential oil of Malaysian Plectranthus Amboinicus (LOUR) spreng as antimalarial in mice - Oothuman, Pakeer (s.n, 2015)

(untitled)
This study was conducted to evaluate the phytochemical content and antimalarial properties of the essential oil from the leaves of Malaysian Plectranthus amboinicus. The essential oil was prepared by using steam distillation technique and subjected to phytochemical screening by using GC-MS. Antimalarial activity of different extract doses of 50, 200, 400 and 1000 µL/kg were tested in vivo against Plasmodium berghei (PZZ1/100) infections in mice (6 mice for each group) during early, established and residual infections. Totally 7 compounds were identified and account for about 88.59% of total oil. The major chemical compounds were carvacrol (85.14%), followed by thymoquinone (1.65%), terpinen-4-ol (0.70%), octenol (0.62%), thymol (0.23%), dioctylazelate (0.15%) and phthalic acid (0.10%). Antimalarial assay suggested this essential oil as a potential prophylactic agent (% chemo suppression: 45.23%, 18.28%, 45.38% and 58.26% while treated with 50, 200, 400 and 1000 µL/kg of essential oil respectively) and curative agent (% chemo suppression: 54.10%, 47.35%, 56.75% and 65.38% while treated with 50, 200, 400 and 1000 µL/kg of essential oil respectively) . Statistically no reduction of parasitemia was seen calculated for suppressive test. Thus, the isolation of active compound of this extract may give a promising drug molecule to be used as prophylactic and curative agent of malaria.